A photovoltaic device and a method of manufacturing the same

CN123021891APending Publication Date: 2026-10-30TRINA SOLAR CO LTD +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611427386.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-09-15
Publication Date
2026-10-30

AI Technical Summary

Technical Problem

该结构在实验室小面积器件中表现优异,但在大面积、绒面织构及长期户外工况下面临严重的界面退化问题,成为制约叠层电池寿命与良率的关键卡点

Benefits of technology

[0029]本发明的空穴传输层中,自组装单分子材料包含的官能团(例如羧基、羟基、氨基、甲硫基等)可以与无机界面层形成化学配位键,将自组装单分子材料牢固地“锚定”在无机界面层上,实现空穴传输层在无机界面层上的化学锚定(上界面锚定),显著提升界面的热稳定性和机械稳定性。进一步地,自组装单分子材料包含的官能团还可以作为成核位点,引导无机界面层在原子级厚度(不大于2nm)的条件下连续致密生长,有效阻隔水氧并钝化界面缺陷,形成物理钝化与化学钝化双重保护,提高无机界面层致密性(即提升钝化效果)。此外,自组装单分子材料中的锚定基团(例如膦酸基)朝向隧穿层,可以与隧穿层表面的金属氧化物(如IZO)形成P-O-M强配位键,实现空穴传输层在隧穿层上的化学锚定。通过这种上下界面双重锚定,自组装单分子材料被牢固固定于两个界面之间,在后续钙钛矿退火结晶(通常>100℃)过程中能够保持稳定的分子取向和排列秩序,避免因热运动导致的分子翻转、脱附或取向紊乱,从而持续提供均匀的成核位点,引导钙钛矿沿最优结晶方向垂直生长,同时维持无机界面层的致密性和界面钝化效果,进而显著提升器件的光电转换效率和热稳定性。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_48
    Figure SMS_48
  • Figure SMS_49
    Figure SMS_49
  • Figure QLYQS_1
    Figure QLYQS_1
Patent Text Reader

Abstract

The application belongs to the field of photovoltaics, and particularly relates to a photovoltaic device and a preparation method thereof. The photovoltaic device comprises, from a light-receiving back surface to a light-receiving front surface, a hole transport layer, an inorganic interface layer and a perovskite light-absorbing layer in sequence, wherein the hole transport layer comprises a self-assembled monomolecular material, and the self-assembled monomolecular material comprises a compound containing a group selected from a hydroxyl group, a carboxyl group, an amino group, a phosphonic acid group and a methylthio group. The photovoltaic device provided by the application has high photoelectric conversion efficiency and a filling factor, is excellent in stability, and has certain industrial application prospects.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of photovoltaics, specifically relating to a photovoltaic device and its preparation method. Background Technology

[0002] The theoretical efficiency limit (Shockley-Queisser limit) of monocrystalline silicon solar cells is approximately 29.4%, and its current mass production efficiency is approaching 26.8%, leaving limited room for further improvement. Perovskite / Si tandem solar cells, through spectral complementarity between a wide-bandgap perovskite top cell (1.68 eV) and a narrow-bandgap silicon bottom cell (1.12 eV), have achieved a theoretical efficiency exceeding 43%, becoming a core technology route for next-generation high-efficiency photovoltaics. In recent years, companies such as Oxford PV, LONGi Green Energy, Jinko Solar, and Tongwei have established GW-level pilot production lines, achieving mass production efficiencies exceeding 30% for tandem modules, and demonstrating significant potential for lower levelized cost of electricity (LCOE) compared to monocrystalline silicon solar cells.

[0003] The industrialization of tandem solar cells is constrained by the interface reliability and process compatibility of the tunneling interconnect layer (ICL). Traditional ICLs typically consist of CVD-prepared n-type microcrystalline silicon (μc-Si:H) + magnetron sputtered transparent conductive oxide (TCO, such as ITO / IZO). This structure performs excellently in small-area laboratory devices, but faces severe interface degradation problems under large-area, textured, and long-term outdoor conditions, becoming a key bottleneck restricting the lifespan and yield of tandem solar cells. Summary of the Invention

[0004] To address the aforementioned problems in the prior art, this invention proposes a photovoltaic device and its fabrication method. The photovoltaic device provided by this invention has high photoelectric conversion efficiency and fill factor, excellent stability, and very high commercial application prospects.

[0005] One aspect of the present invention provides a photovoltaic device comprising, from the back side to the front side, a hole transport layer, an inorganic interface layer and a perovskite light-absorbing layer; the hole transport layer comprises a self-assembled monomolecule material; the self-assembled monomolecule material comprises a compound containing a group selected from hydroxyl, carboxyl, amino, phosphonic acid and methylthio groups.

[0006] In one or more embodiments, the self-assembled monomolecular material comprises a compound containing at least two groups selected from hydroxyl, carboxyl, amino, phosphonic acid, and methylthio groups.

[0007] In one or more embodiments, at least one group selected from hydroxyl, carboxyl, amino, phosphonic acid, and methylthio groups of the compound is an end group of the compound.

[0008] In one or more embodiments, the thickness of the inorganic interface layer is 0.4-2 nm.

[0009] In one or more embodiments, the thickness of the inorganic interface layer is 0.5-1.8 nm.

[0010] In one or more embodiments, the inorganic interface layer material is selected from one or more of inorganic oxides, inorganic halides, inorganic sulfides, inorganic selenides, inorganic nitrides, and inorganic tellurides.

[0011] In one or more embodiments, the inorganic oxide includes one or more selected from aluminum oxide, hafnium oxide, zirconium oxide, titanium oxide, and magnesium oxide.

[0012] In one or more embodiments, the inorganic nitride includes one or more selected from silicon nitride, aluminum nitride, and boron nitride.

[0013] In one or more embodiments, the inorganic halide includes one or more selected from magnesium halides, lithium halides, and aluminum halides.

[0014] In one or more embodiments, the inorganic sulfide includes zinc sulfide.

[0015] In one or more embodiments, the self-assembled monomolecule material has the structure shown in Formula I or Formula II: , In Formula I, R1 and R2 are each independently hydroxyl, carboxyl, amino, or methylthio; R3 is phosphonic acid, sulfonic acid, carboxyl, or boric acid; L1 and L2 are each independently C3-C12 heteroarylene, C6-C12 arylene, C1-C4 alkylene, or absent. , In Formula II, X1, X2, X3, X4, X5, X6, X7, and X8 are each independently a hydrogen atom, hydroxyl group, carboxyl group, amino group, methylthio group, phosphonic acid group, sulfonic acid group, or boric acid group, and at least one group among X1, X2, X3, X4, X5, X6, X7, and X8 is a phosphonic acid group, sulfonic acid group, carboxyl group, or boric acid group; Z is selected from the structure of Formula III ( ) and IV structure ( ),in, For the connection site with the remainder of the compound of formula II, M1 and M2 are each independently selected from C1-C4 alkyl groups; M3 is selected from substituted or unsubstituted C6-C14 aromatic groups, which are optionally substituted by 1, 2, 3, 4 or 5 substituents selected from hydroxyl, carboxyl, amino, methylthio, phosphonic acid, sulfonic acid and boric acid groups.

[0016] In one or more embodiments, in Formula I, L1 and L2 are each independently 2,1,3-benzothiadiazole-4,7-diyl, phenylene, or absent.

[0017] In one or more embodiments, in Formula II, X1, X2, X3, X4, X5, X6, X7, and X8 are each independently a hydrogen atom, hydroxyl group, carboxyl group, amino group, methylthio group, phosphonic acid group, sulfonic acid group, or borate group, and at least one group among X1, X2, X3, X4, X5, X6, X7, and X8 is a phosphonic acid group, sulfonic acid group, carboxyl group, or borate group; Z is selected from the structure of Formula III ( ) and IV structure ( ),in, For the connection site with the remainder of the compound of formula II, M1 and M2 are each independently selected from C1-C4 alkyl groups; M3 is selected from substituted or unsubstituted phenyl groups, which are optionally substituted by 1, 2, 3, 4 or 5 substituents selected from hydroxyl, carboxyl, amino, methylthio, phosphonic acid, sulfonic acid and boric acid groups.

[0018] In one or more embodiments, in Formula II, X1, X2, X3, X4, X5, X6, X7, and X8 are each independently a hydrogen atom, hydroxyl group, carboxyl group, amino group, methylthio group, phosphonic acid group, sulfonic acid group, or borate group, and at least one group among X1, X2, X3, X4, X5, X6, X7, and X8 is a phosphonic acid group, sulfonic acid group, carboxyl group, or borate group; Z is selected from the structure of Formula III ( ) and IV structure ( ),in, For the connection site with the remainder of the compound of formula II, M1 and M2 are each independently selected from C1-C4 alkyl groups; M3 is selected from substituted or unsubstituted phenyl groups, wherein the phenyl group is optionally substituted by one substituent selected from hydroxyl, carboxyl, amino, methylthio, phosphonic acid, sulfonic acid and boric acid groups.

[0019] In one or more embodiments, the compound of formula II is In formula V, X1, X2, X3, X4, X5, X6, X7 and X8 are each independently a hydrogen atom, hydroxyl group, carboxyl group, amino group, methylthio group, phosphonic acid group, sulfonic acid group or borate group; wherein at least three of X1, X2, X3, X4, X5, X6, X7 and X8 are not hydrogen; and at least one of X1, X2, X3, X4, X5, X6, X7 and X8 is a phosphonic acid group, sulfonic acid group, carboxyl group or borate group.

[0020] In one or more embodiments, the compound of formula II is , In Formula VI, Y1, Y2, Y3, Y4, Y5, Y6, Y7, and Y8 are each independently a hydrogen atom, hydroxyl group, carboxyl group, amino group, or methylthio group; Y9 is a phosphonic acid group, sulfonic acid group, carboxyl group, or boric acid group; L3 is a C3-C12 heteroarylene, C6-C12 arylene, C1-C4 alkylene group, or is absent; wherein, at least one group among Y1, Y2, Y3, Y4, Y5, Y6, Y7, and Y8 is not hydrogen.

[0021] In one or more embodiments, in formula VI, L3 is phenylene, C1-C4 alkyl, or absent.

[0022] In one or more embodiments, the self-assembled monomolecule material is selected from: , , and .

[0023] In one or more embodiments, the photovoltaic device is a crystalline silicon-perovskite tandem cell.

[0024] In one or more embodiments, the crystalline silicon-perovskite tandem solar cell comprises, from the light-receiving back side to the light-receiving front side, a crystalline silicon cell, a tunneling layer, a hole transport layer, an inorganic interface layer, a perovskite light-absorbing layer, an electron transport layer, a transparent conductive layer, and a metal electrode.

[0025] In one or more embodiments, a perovskite passivation layer is further provided between the perovskite light-absorbing layer and the electron transport layer.

[0026] In one or more embodiments, the tunneling layer comprises a transparent conductive oxide.

[0027] Another aspect of the present invention provides a method for preparing the photovoltaic device described in any embodiment of the present invention, the method comprising: sequentially preparing a hole transport layer, an inorganic interface layer, and a perovskite light-absorbing layer on a conductive substrate; wherein the inorganic interface layer is prepared by atomic layer deposition or chemical bath deposition; and wherein the temperature at which the inorganic interface layer is deposited is lower than the thermal decomposition temperature of the hole transport layer.

[0028] In one or more embodiments, the conductive substrate includes a tunneling layer and optionally a crystalline silicon cell located on the side of the tunneling layer away from the light-receiving side.

[0029] In the hole transport layer of this invention, the functional groups (e.g., carboxyl, hydroxyl, amino, methylthio groups, etc.) contained in the self-assembled monomolecule material can form chemical coordination bonds with the inorganic interface layer, firmly "anchoring" the self-assembled monomolecule material to the inorganic interface layer. This achieves chemical anchoring (upper interface anchoring) of the hole transport layer on the inorganic interface layer, significantly improving the thermal and mechanical stability of the interface. Furthermore, the functional groups contained in the self-assembled monomolecule material can also serve as nucleation sites, guiding the continuous and dense growth of the inorganic interface layer at an atomic thickness (not greater than 2 nm). This effectively blocks water and oxygen and passivates interface defects, forming dual protection of physical and chemical passivation, improving the density of the inorganic interface layer (i.e., enhancing the passivation effect). In addition, the anchoring groups (e.g., phosphonic acid groups) in the self-assembled monomolecule material, facing the tunneling layer, can form strong POM coordination bonds with the metal oxides (e.g., IZO) on the surface of the tunneling layer, achieving chemical anchoring of the hole transport layer on the tunneling layer. Through this dual anchoring at the upper and lower interfaces, the self-assembled single-molecule material is firmly fixed between the two interfaces. During the subsequent perovskite annealing and crystallization process (usually >100℃), it can maintain a stable molecular orientation and arrangement order, avoiding molecular flipping, desorption, or orientation disorder caused by thermal motion. This continuously provides uniform nucleation sites, guides the perovskite to grow vertically along the optimal crystallization direction, and maintains the density of the inorganic interface layer and the interface passivation effect, thereby significantly improving the photoelectric conversion efficiency and thermal stability of the device. Detailed Implementation

[0030] To enable those skilled in the art to understand the features and effects of the present invention, the terms and expressions used herein are explained and defined in general terms below. Unless otherwise specified, all technical and scientific terms used herein have the common meaning understood by those skilled in the art regarding the present invention, and in case of conflict, the definitions in this specification shall prevail.

[0031] The theories or mechanisms described and disclosed herein, whether right or wrong, should not in any way limit the scope of the invention, that is, the contents of the invention can be implemented without being limited by any particular theory or mechanism.

[0032] In this document, the terms “contains,” “includes,” “containing,” and similar terms encompass the meanings of “basically composed of” and “composed of.” For example, when this document discloses “A contains B and C,” “A is basically composed of B and C” and “A is composed of B and C” should be considered as having been disclosed in this document.

[0033] In this document, all features defined by numerical ranges or percentage ranges, such as numerical values, quantities, contents, and concentrations, are for the sake of brevity and convenience only. Accordingly, descriptions of numerical ranges or percentage ranges should be considered as covering and specifically disclosing all possible sub-ranges and individual numerical values ​​(including integers and fractions) within those ranges.

[0034] Unless otherwise specified, percentages refer to mass percentages and proportions refer to mass ratios in this article.

[0035] In this article, the sum of the percentages of all components in the composition is 100%.

[0036] In this document, when describing embodiments or examples, it should be understood that it is not intended to limit the invention to those embodiments or examples. Rather, all alternatives, modifications, and equivalents of the methods and materials described herein are covered within the scope of this invention.

[0037] For the sake of brevity, not all possible combinations of the technical features in each implementation scheme or embodiment are described herein. Therefore, as long as there is no contradiction in the combination of these technical features, the technical features in each implementation scheme or embodiment can be combined arbitrarily, and all possible combinations should be considered within the scope of this specification.

[0038] Photovoltaic devices

[0039] The photovoltaic device of the present invention comprises, from the back side to the front side, a hole transport layer, an inorganic interface layer and a perovskite light-absorbing layer. The hole transport layer comprises a self-assembled monomolecule material, which includes a compound containing a group selected from hydroxyl, carboxyl, amino, phosphonic acid and methylthio groups.

[0040] In some implementations, the thickness of the inorganic interface layer is 0.4-2 nm, for example, 0.4 nm, 0.5 nm, 0.6 nm, 0.7 nm, 0.8 nm, 0.9 nm, 1 nm, 1.1 nm, 1.2 nm, 1.3 nm, 1.4 nm, 1.5 nm, 1.6 nm, 1.7 nm, 1.8 nm, 1.9 nm, 2 nm, or any range between two values.

[0041] In some preferred embodiments, the thickness of the inorganic interface layer is 0.5-1.8 nm.

[0042] In some implementations, the inorganic interface layer comprises an inorganic interface layer material, which is an insulator or a wide bandgap semiconductor with a bandgap greater than 2.5 eV.

[0043] The inorganic interface layer materials suitable for this invention include, but are not limited to, one or more selected from inorganic oxides, inorganic halides, inorganic sulfides, inorganic selenides, and inorganic tellurides. In some preferred embodiments, the inorganic oxides include, but are not limited to, one or more selected from alumina, hafnium oxide, zirconium oxide, titanium oxide, and magnesium oxide. In some preferred embodiments, the inorganic nitrides include, but are not limited to, one or more selected from silicon nitride, aluminum nitride, and boron nitride. In some preferred embodiments, the inorganic halide is an inorganic fluoride, including, but not limited to, one or more selected from magnesium fluoride, lithium fluoride, and aluminum fluoride. In some preferred embodiments, the inorganic sulfides include, but are not limited to, zinc sulfide.

[0044] In some embodiments, the self-assembled monomolecular material comprises a compound containing at least two groups selected from hydroxyl, carboxyl, amino, phosphonic acid, and methylthio groups.

[0045] In some embodiments, the self-assembled monomolecular material comprises a compound containing two or three groups selected from hydroxyl, carboxyl, amino, phosphonic acid, and methylthio groups.

[0046] In some embodiments, at least one group selected from hydroxyl, carboxyl, amino, phosphonic acid, and methylthio groups in the compound is an end group of the compound.

[0047] The self-assembled monomolecular materials suitable for use in this invention preferably comprise compounds containing at least one phosphonic acid group and one or more (e.g., 1, 2, 3, or 4) groups selected from hydroxyl, carboxyl, amino, and methylthio groups. In some preferred embodiments, the self-assembled monomolecular materials comprise compounds containing one phosphonic acid group and one or more (e.g., 1, 2, 3, or 4) groups selected from hydroxyl, carboxyl, amino, and methylthio groups. In some preferred embodiments, the self-assembled monomolecular materials comprise compounds containing one phosphonic acid group and one or two groups selected from hydroxyl, carboxyl, amino, and methylthio groups.

[0048] This invention provides a compound that can be used as a self-assembled monomolecular material, the compound having the structure shown in Formula I or Formula II: , In Formula I, R1 and R2 are each independently hydroxyl, carboxyl, amino, or methylthio; R3 is phosphonic acid, sulfonic acid, carboxyl, or boric acid; L1 and L2 are each independently C3-C12 heteroarylene, C6-C12 arylene, C1-C4 alkylene, or absent. , In Formula II, X1, X2, X3, X4, X5, X6, X7, and X8 are each independently a hydrogen atom, hydroxyl group, carboxyl group, amino group, methylthio group, phosphonic acid group, sulfonic acid group, or boric acid group, and at least one group among X1, X2, X3, X4, X5, X6, X7, and X8 is a phosphonic acid group, sulfonic acid group, carboxyl group, or boric acid group; Z is selected from the structure of Formula III ( ) and IV structure ( ),in, For the connection site with the remainder of the compound of formula II, M1 and M2 are each independently selected from C1-C4 alkyl groups; M3 is selected from substituted or unsubstituted C6-C14 aromatic groups, which are optionally substituted by 1, 2, 3, 4 or 5 substituents selected from hydroxyl, carboxyl, amino, methylthio, phosphonic acid, sulfonic acid and boric acid groups.

[0049] In some embodiments, the compound represented by Formula I or Formula II includes two or more groups selected from hydroxyl, carboxyl, amino, phosphonic acid, and methylthio groups.

[0050] In some embodiments, the compound represented by Formula I or Formula II includes two or three groups selected from hydroxyl, carboxyl, amino, phosphonic acid, and methylthio groups.

[0051] In some embodiments, the compound represented by Formula I or Formula II comprises at least one phosphonic acid group and one or more (e.g., 1, 2, 3, or 4) groups selected from hydroxyl, carboxyl, amino, and methylthio groups. In some preferred embodiments, the compound represented by Formula I or Formula II comprises one phosphonic acid group and one or two groups selected from hydroxyl, carboxyl, amino, and methylthio groups. In some preferred embodiments, the compound represented by Formula I or Formula II comprises one phosphonic acid group and one or two groups selected from hydroxyl, carboxyl, amino, and methylthio groups.

[0052] In this invention, the hole transport layer or self-assembled monomolecular material may comprise the compounds of Formula I and / or Formula II as described in any of the embodiments herein.

[0053] In some embodiments, in Formula I, R1 and R2 are each independently hydroxyl, carboxyl, amino, or methylthio; L1 and L2 are each independently C3-C12 heteroarylene, C6-C12 arylene, or absent; and R3 is phosphonic acid, sulfonic acid, carboxyl, or boric acid. In some preferred embodiments, R3 is phosphonic acid.

[0054] In some embodiments, in Formula I, R1 and R2 are each independently hydroxyl, carboxyl, amino, or methylthio; L1 and L2 are not present, and R3 is phosphonic acid, sulfonic acid, carboxyl, or boric acid; in some preferred embodiments, R3 is phosphonic acid.

[0055] In some embodiments, in Formula I, R1 and R2 are each independently hydroxyl, carboxyl, amino, or methylthio; L1 and L2 are each independently C3-C12 heteroarylene or C6-C12 arylene; and R3 is phosphonic acid, sulfonic acid, carboxyl, or borate. In some preferred embodiments, R3 is phosphonic acid.

[0056] In some embodiments, in Formula I, R1 and R2 are each independently hydroxyl, carboxyl, amino, or methylthio; L1 and L2 are each independently 2,1,3-benzothiadiazole-4,7-diyl, phenylene, or absent; and R3 is phosphonic acid, sulfonic acid, carboxyl, or borate. In some preferred embodiments, R3 is phosphonic acid.

[0057] In some embodiments, in Formula II, X1, X2, X3, X4, X5, X6, X7, and X8 are each independently a hydrogen atom, hydroxyl group, carboxyl group, amino group, methylthio group, phosphonic acid group, sulfonic acid group, or borate group, and at least one group among X1, X2, X3, X4, X5, X6, X7, and X8 is a phosphonic acid group, sulfonic acid group, carboxyl group, or borate group; Z is selected from the structure of Formula III ( ) and IV structure ( ),in, For the connection site with the remainder of the compound of formula II, M1 and M2 are each independently selected from C1-C4 alkyl groups; M3 is selected from substituted or unsubstituted phenyl groups, which are optionally substituted by 1, 2, 3, 4 or 5 substituents selected from hydroxyl, carboxyl, amino, methylthio, phosphonic acid, sulfonic acid and boric acid groups.

[0058] In some embodiments, in Formula II, X1, X2, X3, X4, X5, X6, X7, and X8 are each independently a hydrogen atom, hydroxyl group, carboxyl group, amino group, methylthio group, phosphonic acid group, sulfonic acid group, or borate group, and at least one group among X1, X2, X3, X4, X5, X6, X7, and X8 is a phosphonic acid group, sulfonic acid group, carboxyl group, or borate group; Z is selected from the structure of Formula III ( ) and IV structure ( ),in, For the connection site with the remainder of the compound of formula II, M1 and M2 are each independently selected from C1-C4 alkyl groups; M3 is selected from substituted or unsubstituted phenyl groups, wherein the phenyl group is optionally substituted by one substituent selected from hydroxyl, carboxyl, amino, methylthio, phosphonic acid, sulfonic acid and boric acid groups.

[0059] In some embodiments, the compound of formula II is In formula V, X1, X2, X3, X4, X5, X6, X7 and X8 are each independently a hydrogen atom, hydroxyl group, carboxyl group, amino group, methylthio group, phosphonic acid group, sulfonic acid group or borate group; wherein at least two groups among X1, X2, X3, X4, X5, X6, X7 and X8 are not hydrogen; and at least one group among X1, X2, X3, X4, X5, X6, X7 and X8 is a phosphonic acid group, sulfonic acid group, carboxyl group or borate group.

[0060] In some embodiments, in formula V, X1, X2, X3, X4, X5, X6, X7, and X8 are each independently a hydrogen atom, a hydroxyl group, a carboxyl group, an amino group, a methylthio group, a phosphonic acid group, a sulfonic acid group, or a borate group; wherein two of X1, X2, X3, X4, X5, X6, X7, and X8 are not hydrogen groups; and at least one of X1, X2, X3, X4, X5, X6, X7, and X8 is a phosphonic acid group, a sulfonic acid group, a carboxyl group, or a borate group.

[0061] In some embodiments, in formula V, X1, X2, X3, X4, X5, X6, X7, and X8 are each independently a hydrogen atom, a hydroxyl group, a carboxyl group, an amino group, a methylthio group, a phosphonic acid group, a sulfonic acid group, or a boric acid group; wherein two of X1, X2, X3, X4, X5, X6, X7, and X8 are not hydrogen groups; and at least one of X1, X2, X3, X4, X5, X6, X7, and X8 is a phosphonic acid group.

[0062] In some embodiments, in formula V, X1, X2, X3, X4, X5, X6, X7, and X8 are each independently a hydrogen atom, a hydroxyl group, a carboxyl group, an amino group, a methylthio group, a phosphonic acid group, a sulfonic acid group, or a borate group; wherein at least three of X1, X2, X3, X4, X5, X6, X7, and X8 are not hydrogen; and at least one of X1, X2, X3, X4, X5, X6, X7, and X8 is a phosphonic acid group, a sulfonic acid group, a carboxyl group, or a borate group.

[0063] In some embodiments, in formula V, X1, X2, X3, X4, X5, X6, X7, and X8 are each independently a hydrogen atom, a hydroxyl group, a carboxyl group, an amino group, a methylthio group, a phosphonic acid group, a sulfonic acid group, or a borate group; wherein at least three of X1, X2, X3, X4, X5, X6, X7, and X8 are not hydrogen; and at least one of X1, X2, X3, X4, X5, X6, X7, and X8 is a phosphonic acid group, a sulfonic acid group, a carboxyl group, or a borate group, and at least one of X1, X2, X3, X4, X5, X6, X7, and X8 is a methylthio group.

[0064] In some embodiments, in formula V, X1, X2, X3, X4, X5, X6, X7, and X8 are each independently a hydrogen atom, a hydroxyl group, a carboxyl group, an amino group, a methylthio group, a phosphonic acid group, a sulfonic acid group, or a borate group; wherein at least three of X1, X2, X3, X4, X5, X6, X7, and X8 are not hydrogen; and at least one of X1, X2, X3, X4, X5, X6, X7, and X8 is a phosphonic acid group, a sulfonic acid group, a carboxyl group, or a borate group, and at least two of X1, X2, X3, X4, X5, X6, X7, and X8 is a methylthio group.

[0065] In some embodiments, in formula V, X1, X2, X3, X4, X5, X6, X7, and X8 are each independently a hydrogen atom, a hydroxyl group, a carboxyl group, an amino group, a methylthio group, a phosphonic acid group, a sulfonic acid group, or a borate group; wherein, three of the groups in X1, X2, X3, X4, X5, X6, X7, and X8 are not hydrogen; and at least one of the groups in X1, X2, X3, X4, X5, X6, X7, and X8 is a phosphonic acid group, a sulfonic acid group, a carboxyl group, or a borate group.

[0066] In some embodiments, in formula V, X1, X2, X3, X4, X5, X6, X7, and X8 are each independently a hydrogen atom, a hydroxyl group, a carboxyl group, an amino group, a methylthio group, a phosphonic acid group, a sulfonic acid group, or a boric acid group; wherein, three of the groups in X1, X2, X3, X4, X5, X6, X7, and X8 are not hydrogen; and at least one of the groups in X1, X2, X3, X4, X5, X6, X7, and X8 is a phosphonic acid group.

[0067] In some embodiments, in formula V, X1, X2, X3, X4, X5, X6, X7, and X8 are each independently a hydrogen atom, a hydroxyl group, a carboxyl group, an amino group, a methylthio group, a phosphonic acid group, a sulfonic acid group, or a boric acid group; wherein, three of the groups in X1, X2, X3, X4, X5, X6, X7, and X8 are not hydrogen; and at least one of the groups in X1, X2, X3, X4, X5, X6, X7, and X8 is a phosphonic acid group and at least one of the groups is a methylthio group.

[0068] In some embodiments, in formula V, X1, X2, X3, X4, X5, X6, X7, and X8 are each independently a hydrogen atom, a hydroxyl group, a carboxyl group, an amino group, a methylthio group, a phosphonic acid group, a sulfonic acid group, or a boric acid group; wherein, three of X1, X2, X3, X4, X5, X6, X7, and X8 are not hydrogen groups; and one of X1, X2, X3, X4, X5, X6, X7, and X8 is a phosphonic acid group, and two of X1, X2, X3, X4, X5, X6, X7, and X8 is a methylthio group.

[0069] In some embodiments, the compound of formula II is , In Formula VI, Y1, Y2, Y3, Y4, Y5, Y6, Y7, and Y8 are each independently a hydrogen atom, hydroxyl group, carboxyl group, amino group, or methylthio group; Y9 is a phosphonic acid group, sulfonic acid group, carboxyl group, or boric acid group; L3 is a C3-C12 heteroarylene, C6-C12 arylene, C1-C4 alkylene group, or is absent; wherein, at least one group among Y1, Y2, Y3, Y4, Y5, Y6, Y7, and Y8 is not hydrogen.

[0070] In some embodiments, in Formula VI, Y1, Y2, Y3, Y4, Y5, Y6, Y7, and Y8 are each independently a hydrogen atom, a hydroxyl group, a carboxyl group, an amino group, or a methylthio group; Y9 is a phosphonic acid group, a sulfonic acid group, a carboxyl group, or a boric acid group; L3 is a C6-C12 arylene, a C1-C4 alkylene group, or is absent; wherein at least one of Y1, Y2, Y3, Y4, Y5, Y6, Y7, and Y8 is not hydrogen.

[0071] In some embodiments, in Formula VI, Y1, Y2, Y3, Y4, Y5, Y6, Y7, and Y8 are each independently a hydrogen atom, a hydroxyl group, a carboxyl group, an amino group, or a methylthio group; Y9 is a phosphonic acid group, a sulfonic acid group, a carboxyl group, or a boric acid group; L3 is a phenylene group, a C1-C4 alkylene group, or is absent; wherein at least one of Y1, Y2, Y3, Y4, Y5, Y6, Y7, and Y8 is not hydrogen.

[0072] In some embodiments, in Formula VI, Y1, Y2, Y3, Y4, Y5, Y6, Y7 and Y8 are each independently a hydrogen atom, hydroxyl group, carboxyl group, amino group or methylthio group; Y9 is a phosphonic acid group, sulfonic acid group, carboxyl group or boric acid group; L3 is a phenylene group; wherein at least one of Y1, Y2, Y3, Y4, Y5, Y6, Y7 and Y8 is not hydrogen.

[0073] In some embodiments, in Formula VI, Y1, Y2, Y3, Y4, Y5, Y6, Y7 and Y8 are each independently a hydrogen atom, hydroxyl group, carboxyl group, amino group or methylthio group; Y9 is a phosphonic acid group, sulfonic acid group, carboxyl group or boric acid group; L3 is a phenylene group; wherein at least one of Y1, Y2, Y3, Y4, Y5, Y6, Y7 and Y8 is a carboxyl group.

[0074] In some embodiments, in Formula VI, Y1, Y2, Y3, Y4, Y5, Y6, Y7 and Y8 are each independently a hydrogen atom, hydroxyl group, carboxyl group, amino group or methylthio group; Y9 is a phosphonic acid group, sulfonic acid group, carboxyl group or boric acid group; L3 is a phenylene group; wherein only one group among Y1, Y2, Y3, Y4, Y5, Y6, Y7 and Y8 is a carboxyl group.

[0075] In some embodiments, in Formula VI, Y1, Y2, Y3, Y4, Y5, Y6, Y7 and Y8 are each independently a hydrogen atom, hydroxyl group, carboxyl group, amino group or methylthio group; Y9 is a phosphonic acid group, sulfonic acid group, carboxyl group or boric acid group; L3 is a phenylene group; wherein, only one group among Y1, Y2, Y3, Y4, Y5, Y6, Y7 and Y8 is a carboxyl group, and the remaining groups are hydrogen atoms.

[0076] In some implementations, the self-assembled monomolecule material is selected from: , , and .

[0077] In some embodiments, the self-assembled monomolecular material is The inorganic interface layer material is selected from one or more of alumina, hafnium oxide, zirconium oxide, titanium oxide, and zinc sulfide.

[0078] In some embodiments, the self-assembled monomolecular material is The inorganic interface layer material is titanium oxide.

[0079] In some embodiments, the self-assembled monomolecular material is The inorganic interface layer material is selected from one or more of alumina, hafnium oxide, zirconium oxide, titanium oxide, and zinc sulfide.

[0080] In some embodiments, the self-assembled monomolecular material is The inorganic interface layer material is zirconium oxide.

[0081] In some embodiments, the self-assembled monomolecule material is The inorganic interface layer material is selected from one or more of alumina, hafnium oxide, zirconium oxide, titanium oxide, and zinc sulfide.

[0082] In some embodiments, the self-assembled monomolecular material is The inorganic interface layer material is zinc sulfide.

[0083] In some embodiments, the self-assembled monomolecular material is The inorganic interface layer material is selected from one or more of alumina, hafnium oxide, zirconium oxide, titanium oxide, and zinc sulfide.

[0084] In some embodiments, the self-assembled monomolecular material is The inorganic interface layer material is hafnium oxide.

[0085] In some embodiments, the perovskite solar cell is a crystalline silicon-perovskite tandem cell.

[0086] In some embodiments, the crystalline silicon-perovskite tandem solar cell comprises, from the light-receiving back side to the light-receiving front side, a crystalline silicon cell, a tunneling layer, a hole transport layer, an inorganic interface layer, a perovskite light-absorbing layer, an electron transport layer, a transparent conductive layer, and a metal electrode.

[0087] In some embodiments, a perovskite passivation layer is further provided between the perovskite light-absorbing layer and the electron transport layer.

[0088] In some embodiments, the tunneling layer comprises a transparent conductive oxide.

[0089] Methods for fabricating photovoltaic devices

[0090] The method for fabricating photovoltaic devices according to the present invention includes: sequentially fabricating a hole transport layer, an inorganic interface layer, and a perovskite light-absorbing layer on a conductive substrate; the inorganic interface layer is prepared by atomic layer deposition or chemical bath deposition; the temperature at which the inorganic interface layer is deposited is lower than the thermal decomposition temperature of the hole transport layer.

[0091] In some preferred embodiments, the conductive substrate includes a tunneling layer and optionally a crystalline silicon cell located on the side of the tunneling layer away from the light-receiving side.

[0092] application

[0093] The present invention also provides the application of the photovoltaic device described in any embodiment of the present invention in improving the stability and / or efficiency of photovoltaic modules.

[0094] The present invention will be described below by way of specific embodiments. It should be understood that these embodiments are merely illustrative and are not intended to limit the scope of the invention. The methods, reagents, and materials used in the embodiments and comparative examples are conventional methods, reagents, and materials in the art, unless otherwise stated. The starting material compounds in the embodiments and comparative examples are all commercially available.

[0095] Synthesis example 1

[0096] Step 1: Synthesis of intermediate ester (CN coupling)

[0097] Under nitrogen protection, the following were added to a 250 mL three-necked flask: 4,4'-diaminodiphenylamine (10.0 g, 50.4 mmol), diethyl(4-bromophenyl)phosphonate (15.8 g, 55.4 mmol), Pd2(dba)3 (1.15 g, 1.26 mmol), 2-dicyclohexylphosphine-2',4',6'-triisopropylbiphenyl (XPhos) (1.20 g, 2.52 mmol), NaOtBu (7.25 g, 75.6 mmol), and anhydrous toluene (200 mL). The mixture was magnetically stirred and the nitrogen atmosphere was replaced three times. The reaction was carried out at 100 °C for 12 h (TLC monitoring, petroleum ether (PE):ethyl acetate (EA) = 2:1, Rf≈0.4). After the reaction was complete, the mixture was cooled to room temperature, filtered through a diatomaceous earth mat, and the solvent was removed by rotary evaporation under reduced pressure. The crude product was purified by silica gel column chromatography (PE:EA = 3:1 gradient elution), the target fraction was collected, and concentrated under reduced pressure to obtain a pale yellow solid intermediate, diethyl{4-[bis(4-aminophenyl)amino]phenyl}phosphonate, with a yield of 76%.

[0098] Step 2: Phosphonate hydrolysis and purification (deprotection)

[0099] The intermediate obtained in step 1 (10.0 g, 23.8 mmol) was dissolved in anhydrous dichloromethane (100 mL) and cooled to 0°C in an ice-water bath. Trimethylbromosilane (TMSBr, 15.0 mL, 114 mmol) was slowly added dropwise. After the addition was complete, the ice bath was removed, and the mixture was brought to room temperature and stirred for 4 h. Volatile silane byproducts and solvents were removed by vacuum distillation. Anhydrous methanol (50 mL) and deionized water (10 mL) were added to the residue, and the residue was quenched by stirring at room temperature for 2 h. The mixture was concentrated to dryness under reduced pressure. The crude product was recrystallized twice with anhydrous ethanol / water (v / v = 4:1) and dried under vacuum (40°C, 12 h) to obtain a white powder compound 1. The yield was 85%, and the HPLC purity was ≥98.5%. Its mass spectrometry result was m / z: 356.1 [M+H]. + , 378.1 [M+Na] + ; 1 H NMR (400 MHz, DMSO-d6): δ 10.28 (br s, 2H), 7.64 (d, J=8.4 Hz, 2H), 7.56 (d, J=8.4 Hz, 2H), 6.72 (d, J=8.8 Hz, 4H), 6.59 (d, J=8.8Hz, 4H), 5.14 (s, 4H).

[0100] Synthesis example 2

[0101] Step 1: Synthesis of intermediate esters (Suzuki-Miyaura coupling)

[0102] Under nitrogen protection, the following were added to a 250 mL three-necked flask: 4-bromo-7-[4-(diethoxyphosphono)phenyl]benzo[c][1,2,5]thiadiazole (8.5 g, 20.0 mmol), N,N-bis(4-hydroxyphenyl)-4-(4,4,5,5-tetramethyl-1,3,2-dioxoborane-2-yl)aniline (9.2 g, 22.0 mmol), Pd(PPh3)4 (1.15 g, 1.0 mmol), and K2CO3 (5.5 g, 40.0 mmol). Anhydrous THF / deionized water (v / v = 4:1, 150 mL) was added, and the mixture was magnetically stirred and the nitrogen atmosphere was replaced three times. The mixture was heated to 85 °C and reacted for 16 h (TLC monitoring, developing solvent dichloromethane (DCM):methanol (MeOH) = 15:1, Rf ≈ 0.35). After the reaction was completed and cooled to room temperature, the product was filtered through a diatomaceous earth filter, and the solvent was removed by rotary evaporation under reduced pressure. The crude product was purified by silica gel column chromatography (DCM:MeOH = 20:1 gradient elution), and the target fraction was collected and concentrated under reduced pressure to give a yellow solid intermediate, diethyl{4-[4-(bis(4-hydroxyphenyl)amino)phenyl]-7-(4-(diethoxyphosphono)phenyl)benzo[c][1,2,5]thiadiazole} ester, in 76% yield.

[0103] Step 2: Phosphonate hydrolysis and purification (deprotection)

[0104] The intermediate obtained in step 1 (8.0 g, 12.5 mmol) was dissolved in anhydrous dichloromethane (80 mL) and cooled to 0°C in an ice-water bath. Trimethylbromosilane (TMSBr, 8.5 mL, 65.0 mmol) was slowly added dropwise. After the addition was complete, the ice bath was removed, and the mixture was stirred at room temperature for 6 h. Volatile silane byproducts and solvents were removed by vacuum distillation. Anhydrous methanol (40 mL) and deionized water (8 mL) were added to the residue, and the residue was quenched by stirring at room temperature for 2 h. The mixture was concentrated to dryness under reduced pressure. The crude product was recrystallized twice with anhydrous ethanol / water (v / v = 3:1) and dried under vacuum (40°C, 12 h) to give compound 2 (2). The yield was 85%, and the HPLC purity was ≥99.0%. Its mass spectrometry result was m / z: 568.1 [M+H]. + , 590.1 [M+Na] + 566.1 [MH] - ; 1H NMR (400 MHz, DMSO-d6): δ 10.85 (br s, 2H), 9.72 (br s, 2H), 8.12 (d, J=7.6 Hz, 1H), 8.05 (d, J=7.6 Hz, 1H), 7.98 (d, J=8.4 Hz, 2H), 7.68 (d, J=8.4 Hz, 2H), 7.52 (d, J=8.4 Hz, 2H), 7.18 (d, J=8.8Hz, 4H), 6.75 (d, J=8.8 Hz, 4H), 6.62 (d, J=8.4 Hz, 2H).

[0105] Synthesis example 3

[0106] Step 1: Synthesis of intermediate bromide (electrophilic substitution)

[0107] Under nitrogen protection, 2,7-bis(methylthio)-9,9-dimethyl-9H-fluorene (10.0 g, 33.5 mmol) was added to a 250 mL three-necked flask and dissolved in anhydrous dichloromethane (150 mL). The flask was cooled to 0 °C in an ice-water bath, and N-bromosuccinimide (NBS, 6.0 g, 33.5 mmol) was slowly added. After the addition was complete, the ice bath was removed, and the mixture was brought to room temperature and stirred for 4 h (TLC monitoring, developing solvent PE:EA = 10:1, Rf ≈ 0.5). After the reaction was complete, the mixture was quenched with saturated sodium sulfite solution (50 mL), and the phases were separated. The aqueous phase was extracted with dichloromethane (50 mL × 2). The organic phases were combined, dried over anhydrous sodium sulfate, and concentrated under reduced pressure. The crude product was purified by silica gel column chromatography (PE:EA = 20:1 gradient elution), and the target fraction was collected and concentrated under reduced pressure to give a white solid intermediate, 4-bromo-2,7-bis(methylthio)-9,9-dimethyl-9H-fluorene, in 82% yield.

[0108] Step 2: Synthesis of phosphine oxide (Pd-catalyzed CP coupling)

[0109] Under nitrogen protection, the following were added to a 100 mL three-necked flask: the bromide obtained in step 1 (8.0 g, 21.3 mmol), dimethylphosphine oxide (HP(O)Me2, 2.0 g, 25.6 mmol), Pd(OAc)2 (0.24 g, 1.06 mmol), XPhos (1.0 g, 2.13 mmol), and K3PO4 (6.8 g, 32.0 mmol). Anhydrous toluene (80 mL) was added, and the mixture was magnetically stirred and the nitrogen atmosphere was replaced three times. The temperature was raised to 110 °C and the reaction was carried out for 16 h (TLC monitoring, developing solvent DCM:MeOH = 10:1, Rf ≈ 0.4). After the reaction was completed, the mixture was cooled to room temperature, filtered through a diatomaceous earth mat, and the solvent was removed by rotary evaporation under reduced pressure. The crude product was purified by silica gel column chromatography (DCM:MeOH = 15:1 gradient elution), and the target fraction was collected and concentrated under reduced pressure to obtain a pale yellow solid compound 3. The yield was 73%, and the HPLC purity was ≥98.0%. Its mass spectrometry result was m / z: 393.1 [M+H]. + , 415.1 [M+Na] + ; 1 H NMR (400 MHz, DMSO-d6): δ 10.85 (br s, 2H), 7.78 (d, J =2.0 Hz, 1H), 7.66 (dd, J =2.0 Hz, 1H), 7.54 (d, J = 8.0 Hz, 1H), 7.38 (d, J =2.0 Hz, 1H), 7.16 (d, J = 2.0 Hz, 1H), 2.52 (s, 3H), 2.45 (s, 3H), 1.64 (s, 6H).

[0110] Synthesis example 4

[0111] Step 1: Synthesis of diester intermediate (Buchwald-Hartwig CN coupling)

[0112] Under nitrogen protection, the following were added to a 250 mL three-necked flask: ethyl 9H-carbazole-3-acid (10.0 g, 41.8 mmol), diethyl 4-bromophenylphosphonate (12.8 g, 46.0 mmol), Pd2(dba)3 (0.95 g, 1.05 mmol), t-BuXPhos (1.75 g, 4.18 mmol), and NaOtBu (6.0 g, 62.7 mmol). Anhydrous toluene (200 mL) was added, and the mixture was magnetically stirred and the nitrogen atmosphere was replaced three times. The mixture was heated to 100 °C and reacted for 12 h (TLC monitoring, developing solvent PE:EA = 1:1, Rf ≈ 0.3). After the reaction was complete, the mixture was cooled to room temperature, filtered through a diatomaceous earth mat, and the solvent was removed by rotary evaporation under reduced pressure. The crude product was purified by silica gel column chromatography (PE:EA = 2:1 gradient elution), the target fraction was collected, and concentrated under reduced pressure to obtain a pale yellow solid intermediate, ethyl 9-(4-(diethoxyacyl)phenyl)-9H-carbazole-3-carboxylate, with a yield of 80%.

[0113] Step 2: Double hydrolysis and purification (deprotection)

[0114] The intermediate obtained in step 1 (10.0 g, 22.5 mmol) was dissolved in anhydrous dichloromethane (100 mL) and cooled to 0°C in an ice-water bath. Trimethylbromosilane (TMSBr, 15.0 mL, 115 mmol) was slowly added dropwise. After the addition was complete, the ice bath was removed, and the mixture was heated to room temperature and stirred for 12 h. Subsequently, 6M HCl aqueous solution (50 mL) was added, and the mixture was refluxed and stirred for 4 h. The mixture was concentrated under reduced pressure to remove volatile silane byproducts and solvent. Deionized water (50 mL) was added to the residue, resulting in the precipitation of a large amount of white precipitate. The precipitate was collected by filtration, washed three times with cold water, and dried under vacuum (60°C, 12 h) to obtain a white powdery compound 4 ( The yield was 88%, and the HPLC purity was ≥99.2%. Its mass spectrometry result was m / z: 380.1 [M+H]. + , 402.1 [M+Na] + 378.1 [MH] - ; 1H NMR (400 MHz, DMSO-d6): δ 13.15 (br s, 1H), 9.85 (br s, 2H), 8.25 (d, J=1.5 Hz, 1H), 8.12 (dd, J=8.5, 1.5 Hz, 1H), 7.95 (d, J=8.5 Hz, 1H), 7.82 (d,J=8.8 Hz, 2H), 7.65 (d, J=8.8 Hz, 2H), 7.55 (d, J=8.2 Hz, 1H), 7.45 (t, J=7.5Hz, 1H), 7.35 (t, J=7.5 Hz, 1H), 7.25 (d, J=8.2 Hz, 1H).

[0115] Synthesis example 5

[0116] Compound 5 of this synthesis example was prepared using a method similar to that used in Synthesis Example 4. The difference lies in replacing 9H-carbazole-3-oic acid ethyl ester with an equimolar amount of 9H-carbazole-3-phosphate diethyl ester. Its mass spectrometry result is m / z: 404.1 [M+H] + , 426.1 [M+Na] + 402.1 [MH] - ; 1 H NMR (400 MHz, DMSO-d6): δ 12.80 (br s, 4H), 8.18 (d, J=7.6 Hz, 1H), 8.08 (d, J=7.8 Hz, 1H), 7.88 (d, J=2.0 Hz, 1H), 7.78 (d, J=8.5Hz, 2H), 7.62 (dd, J=7.6, 2.0 Hz, 1H), 7.48 (t, J=7.5 Hz, 1H), 7.42 (t, J=7.5Hz, 1H), 7.35 (d, J=8.2 Hz, 1H), 7.12 (d, J=8.5 Hz, 2H).

[0117] Example 1

[0118] This embodiment provides a perovskite / crystalline silicon tandem solar cell module, and the specific fabrication steps are as follows: (1) Preparation of bottom battery Plasma-enhanced chemical vapor deposition (PECVD) was used to deposit intrinsic amorphous silicon layers (a-Si(i)) on both sides of the intrinsic silicon layer (c-Si(n)) at 220℃ to form an amorphous silicon passivation layer. Then, n-type microcrystalline silicon layers and p-type microcrystalline silicon layers were deposited on both sides of the amorphous silicon passivation layer to form an electron transport layer (nc-Si(n)) and a hole transport layer (nc-Si(p)) respectively, resulting in a bottom cell with a thickness of 280 μm. (2) Fabrication of back electrode and tunneling layer ITO was deposited on the surface of a p-type microcrystalline silicon layer using magnetron sputtering to form a transparent conductive layer with a thickness of 85 nm. Silver paste was then printed on the surface of the transparent conductive layer using screen printing to form silver gate electrodes with a height of 10 μm and a width of 50 μm. The transparent conductive layer ITO and the silver gate electrodes together form the back electrode. IZO was deposited on the surface of an n-type microcrystalline silicon layer using radio frequency sputtering to form a tunneling layer with a thickness of 15 nm. This tunneling layer serves as the hole extraction substrate for the top cell, and its surface roughness Ra ≤ 1.2 nm. (3) Preparation of hole transport layer Compound 1 was dissolved in anhydrous ethanol to prepare a 0.2 mmol / mL solution of compound 1; 50 μL of the compound 1 solution was dropped onto the surface of the IZO tunneling layer prepared in step (2), and spin-coated at 4000 rpm for 30 s; after spin-coating, the layer was transferred to a 100℃ heating plate for annealing for 10 min, and after cooling, a hole transport layer with a thickness of 1.5 nm was obtained. (4) Preparation of inorganic interface layer The sample was transferred to an atomic layer deposition (ALD) chamber, and ALD deposition was performed using TDMAT (tetra(dimethylamino)titanium) as the titanium precursor and H2O as the oxygen source at a process temperature of 80℃. After 10 cycles, an ultrathin TiO2 layer with a thickness of 1.2 nm was obtained. (5) Preparation of perovskite light-absorbing layer Using N,N-dimethylformamide (DMF) and dimethyl sulfoxide (DMSO) at a volume ratio of 4:1 as solvent, and PbI₂, PbBr₂, FAI, MABr, and CsI as raw materials, a solution with a concentration of 1.4 mol / L and a composition of CsI was prepared. 0.05 MA 0.08 FA 0.87 Pb(I 0.80 Br 0.20)3 Perovskite precursor solution; perovskite thin film layer was prepared by anti-solvent method: 60 μL of perovskite precursor solution was dropped onto the surface of the inorganic interface layer prepared in step (4) in a nitrogen glove box (H2O<0.1ppm, O2<0.5ppm). The first stage was spin-coated at 1500 rpm for 5 s, and the second stage was spin-coated at 4000 rpm for 25 s. When spin-coating reached the 10th s of the second stage, 200 μL of chlorobenzene anti-solvent was dropped onto its surface. After spin-coating, it was annealed on a hot stage at 110℃ for 15 min to obtain a perovskite light-absorbing layer with a thickness of 500 nm. (6) Preparation of perovskite passivation layer (upper interface passivation) Phenylacetium iodide (PEAI) was dissolved in isopropanol (IPA) to prepare a 1.0 mg / mL solution. The solution was spin-coated at 3500 rpm for 30 s in a nitrogen glove box and then annealed on a hot plate at 90 °C for 5 min to obtain a perovskite passivation layer with a thickness of 8 nm. (7) Fabrication of electron transport layer Fullerene (C) was deposited on the surface of the perovskite passivation layer using a thermal evaporation method (evaporation source temperature 400℃, evaporation rate 0.8 Å / s). 60 A fullerene layer with a thickness of 20 nm was obtained. (8) Preparation of transparent conductive layer A 100 nm thick transparent conductive layer IZO was prepared on the surface of the electron transport layer using reactive plasma deposition (RPD) with a deposition power of 1.5 kW, an oxygen partial pressure of 0.15 Pa, and a substrate temperature of ≤60℃. (9) Fabrication of metal electrodes and antireflection layers Silver was deposited on the surface of a transparent conductive layer using a thermal evaporation method, resulting in a layer with a height of 400 nm and an effective area of ​​1.0 cm². 2 The top electrode is formed; MgF2 is deposited on the periphery of the top electrode and the edge of the module by thermal evaporation to obtain an antireflection layer with a thickness of 120 nm; after laser etching isolation, a perovskite / crystalline silicon tandem solar cell module is obtained.

[0119] Example 2

[0120] The other conditions in this embodiment are the same as in embodiment 1. The only difference is that in step (3) of this embodiment, compound 1 is replaced with an equimolar amount of compound 2; in step (4), the sample is transferred to the atomic layer deposition (ALD) chamber, and ALD deposition is performed at a process temperature of 70°C using TEAZ (zirconium ethanolamine complex) as the zirconium precursor and H2O as the oxygen source. The process is repeated 15 times to obtain an ultrathin ZrO2 layer with a thickness of 1.8 nm.

[0121] Example 3

[0122] The other conditions in this embodiment are the same as in Example 1, except that in step (3) of this embodiment, compound 1 is replaced with an equimolar amount of compound 3. In step (4), the sample is transferred to an atomic layer deposition (ALD) chamber, and ALD deposition is performed using ZnAc2 and Na2S as precursors at a process temperature of 45°C for 15 cycles to obtain an ultrathin ZnS layer with a thickness of 1.8 nm.

[0123] Example 4

[0124] The other conditions in this embodiment are the same as in Example 1, except that in step (3) of this embodiment, compound 1 is replaced with an equimolar amount of compound 4. In step (4), the sample is transferred to an atomic layer deposition (ALD) chamber, and ALD deposition is performed using TEMAH (tetra(ethylmethylamino)hafnium) as the hafnium precursor and H2O as the oxygen source at a process temperature of 90°C for 10 cycles to obtain an ultrathin HfO2 layer with a thickness of 1.5 nm.

[0125] Example 5

[0126] The other conditions in this embodiment are the same as in Example 1, except that in step (3) of this embodiment, compound 1 is replaced with an equimolar amount of compound 4. In step (4), the sample is transferred to an atomic layer deposition (ALD) chamber, and ALD deposition is performed at a process temperature of 85°C using TMA (trimethylaluminum) as the aluminum precursor and H2O as the oxygen source. The cycle is repeated 5 times to obtain an ultrathin Al2O3 layer with a thickness of 0.5 nm.

[0127] Example 6

[0128] The other conditions in this embodiment are the same as in Example 1, except that in step (3) of this embodiment, compound 1 is replaced with an equimolar amount of compound 2. In step (4), the sample is transferred to an atomic layer deposition (ALD) chamber, and ALD deposition is performed at a process temperature of 100°C using trimethylaluminum (TMA) as the aluminum precursor and anhydrous hydrogen fluoride (HF) as the fluorine source. The process is repeated 8 times to obtain an ultrathin AlF3 layer with a thickness of 1.0 nm.

[0129] Example 7

[0130] The other conditions in this embodiment are the same as in Example 1, except that in step (3) of this embodiment, compound 1 is replaced with an equimolar amount of compound 3. In step (4), the sample is transferred to an atomic layer deposition (ALD) chamber, and ALD deposition is performed using trimethylaluminum (TMA) as the aluminum precursor and ammonia (NH3) as the nitrogen source at a process temperature of 150°C in plasma-enhanced mode. The process is repeated 10 times to obtain an ultrathin AlN layer with a thickness of 1.1 nm.

[0131] Comparative Example 1

[0132] The other conditions of this comparative example are the same as those of Example 1, except that in step (3) of this example, compound 1 is replaced with an equimolar amount of (4-(3,6-dimethyl-9H-carbazole-9-yl)butyl)phosphonic acid (Me-4PACz, Biolight).

[0133] Comparative Example 2

[0134] The other conditions of this comparative example are the same as those of Example 1, except that in step (3) of this example, compound 1 is replaced with an equimolar amount of compound 5.

[0135] I. Photovoltaic performance testing: At 25 ℃, AM1.5 standard solar spectrum, and irradiance of 1000 W / m² 2 Under the conditions of open circuit voltage, short circuit current density, fill factor and photoelectric conversion efficiency, the performance of perovskite / crystalline silicon tandem solar cell modules in each embodiment and comparative example was measured using a solar simulator with the voltage range set from 1.85 to -0.1V. The specific test results are shown in Table 1.

[0136] (1) Open circuit voltage (Voc): The voltage value corresponding to the current being zero.

[0137] (2) Short-circuit current density (Jsc): The current value when the voltage is zero is the short-circuit current (Isc), and the current on a unit cell surface area is the short-circuit current density.

[0138] (3) Fill factor (FF): The ratio of the battery’s maximum output power (Pmax) to the product of the open-circuit voltage and the short-circuit current. The formula is (Pmax / Voc×Isc), where the maximum power point is the point where the battery’s output power reaches its maximum value.

[0139] (4) Photoelectric conversion efficiency (PCE): Photoelectric conversion efficiency refers to the ratio of maximum output power to incident light power (Pin), and the calculation formula is (Pmax / Pin)×100%.

[0140] Table 1: Photovoltaic performance test results of perovskite solar cells in each embodiment and comparative example

[0141] Comparative Example 1 used commercially available Me-4PACz as a self-assembled monomolecule material. Its molecular structure contains only one phosphonic acid group and lacks the hydroxyl, carboxyl, amino, or methylthio groups described in this invention. Therefore, it cannot form chemical coordination bonds with the inorganic interface layer, resulting in a lack of upper interface anchoring. Consequently, the inorganic interface layer lacks nucleation sites on the hole transport layer surface, leading to decreased compactness and passivation effects. The flyback factor (FF) of Comparative Example 1 was only 75.81%, and the permeability coefficient (PCE) was only 29.92%, both lower than that of Example 1 (FF=76.52%, PCE=30.58%), which used the same inorganic interface layer (TiO2). Simultaneously, the Voc of Comparative Example 1 was 1.949V, lower than the 1.956V of Example 1, and the Jsc was 20.25 mA / cm². 2 This is lower than the 20.43 mA / cm² in Example 1. 2 This indicates that the increased interface defects and decreased passivation effect caused by the lack of upper interface anchoring have adversely affected the initial photovoltaic performance of the device.

[0142] Comparative Example 2 uses Compound 5 as a self-assembled monomolecular material. Its molecular structure contains two phosphonic acid groups, but does not contain the hydroxyl, carboxyl, amino, or methylthio groups described in this invention. Although Compound 5 can be anchored to the tunneling layer surface via its phosphonic acid groups, the side facing the inorganic interface layer also contains phosphonic acid groups. Its coordination ability and nucleation guidance effect with the inorganic interface layer deposited by ALD are weaker than those of the hydroxyl, carboxyl, amino, or methylthio groups contained in the self-assembled monomolecular material of this invention, thus failing to achieve differentiated anchoring at the upper and lower interfaces. Comparative Example 2 had a photoelectric effect (FF) of only 73.03% and a photoelectric conversion efficiency (PCE) of only 28.96%, both the lowest among all samples. These were 3.49 and 1.62 percentage points lower than Example 1 (FF=76.52%, PCE=30.58%), which used the same inorganic interface layer (TiO2), respectively. Although its Voc was 1.961V, similar to Example 4 (Compound 4, Voc=1.962V) (difference of only 10mV), its Jsc was only 20.22 mA / cm². 2 The value was the lowest among all samples, indicating that the lack of functional groups such as hydroxyl, carboxyl, amino, or methylthio groups leads to uneven nucleation and growth of the inorganic interface layer and an increased interface defect density, which severely restricts the photoelectric conversion performance of the device.

[0143] II. Stability Testing: At 25 ℃, AM1.5 standard solar spectrum, and irradiance of 1000 W / m² 2Under the following conditions, using a solar simulator, with the voltage range set from 1.85 to -0.1V, the performance (open-circuit voltage, short-circuit current density, fill factor, and photoelectric conversion efficiency) of the perovskite / crystalline silicon tandem solar cell modules in each embodiment and comparative example after aging was measured. The aging conditions were: aging at 85°C, 1 sun light intensity, N2 environment, with the cells in Voc state for 24 hours.

[0144] Table 2: Stability test results of perovskite solar cells in each embodiment and comparative example

[0145] Comparative Example 1 used commercially available Me-4PACz as a self-assembled monomolecule material. Its molecular structure contains only one phosphonic acid group and lacks the hydroxyl, carboxyl, amino, or methylthio groups described in this invention. Therefore, it cannot form chemical coordination bonds with the inorganic interface layer, resulting in a lack of upper interface anchoring. Consequently, the inorganic interface layer lacks nucleation sites on the hole transport layer surface, leading to decreased compactness and passivation effects. After aging, Voc decreased from 1.949V to 1.676V (a decrease of 0.273V), significantly greater than the 0.084V in Example 1, indicating severely insufficient interfacial thermal stability.

[0146] Comparative Example 2 uses compound 5 as a self-assembled monomolecule material. Its molecular structure contains two phosphonic acid groups, but lacks the hydroxyl, carboxyl, amino, or methylthio groups described in this invention. Although compound 5 can be anchored to the tunneling layer surface via its phosphonic acid groups, the side facing the inorganic interface layer also contains phosphonic acid groups. Its coordination ability and nucleation guidance effect with the inorganic interface layer deposited by ALD are weaker than those of the hydroxyl, carboxyl, amino, or methylthio groups contained in the self-assembled monomolecule material of this invention, thus failing to achieve differentiated anchoring of the upper and lower interfaces. Comparative Example 2 showed a PCE of only 23.53% after aging, the lowest among all samples, and a Voc decrease of 0.312V after aging, further confirming the crucial role of the self-assembled monomolecule material of this invention in achieving dual anchoring of the upper and lower interfaces and maintaining interfacial thermal stability.

[0147] In summary, the self-assembled monomolecule material defined in this invention achieves significantly better photoelectric conversion efficiency and interface stability than the comparative example through a dual anchoring mechanism at the upper and lower interfaces.

Claims

1. A photovoltaic device, characterized in that, The photovoltaic device comprises, from the back side to the front side, a hole transport layer, an inorganic interface layer, and a perovskite light-absorbing layer; the hole transport layer comprises a self-assembled monomolecule material; the self-assembled monomolecule material comprises a compound containing a group selected from hydroxyl, carboxyl, amino, phosphonic acid, and methylthio groups.

2. The photovoltaic device as described in claim 1, characterized in that, The self-assembled monomolecular material includes compounds containing at least two groups selected from hydroxyl, carboxyl, amino, phosphonic acid, and methylthio groups.

3. The photovoltaic device as described in claim 1, characterized in that, At least one of the groups selected from hydroxyl, carboxyl, amino, phosphonic acid, and methylthio groups in the compound is a terminal group of the compound.

4. The photovoltaic device as described in claim 1, characterized in that, The thickness of the inorganic interface layer is 0.4-2 nm.

5. The photovoltaic device as described in claim 1, characterized in that, The thickness of the inorganic interface layer is 0.5-1.8 nm.

6. The photovoltaic device as described in claim 1, characterized in that, The inorganic interface layer material is selected from one or more of inorganic oxides, inorganic halides, inorganic sulfides, inorganic selenides, inorganic nitrides, and inorganic tellurides.

7. The photovoltaic device as described in claim 6, characterized in that, The inorganic interface layer material has one or more of the following characteristics: The inorganic oxides include one or more selected from aluminum oxide, hafnium oxide, zirconium oxide, titanium oxide, and magnesium oxide; The inorganic nitrides include one or more selected from silicon nitride, aluminum nitride, and boron nitride; The inorganic halide includes one or more selected from magnesium fluoride, lithium fluoride and aluminum fluoride; The inorganic sulfides include zinc sulfide.

8. The photovoltaic device as described in claim 1, characterized in that, The self-assembled monomolecule material has the structure shown in Formula I or Formula II: , In Formula I, R1 and R2 are each independently hydroxyl, carboxyl, amino, or methylthio; R3 is phosphonic acid, sulfonic acid, carboxyl, or boric acid; L1 and L2 are each independently C3-C12 heteroarylene, C6-C12 arylene, C1-C4 alkylene, or absent. , In Formula II, X1, X2, X3, X4, X5, X6, X7, and X8 are each independently a hydrogen atom, hydroxyl group, carboxyl group, amino group, methylthio group, phosphonic acid group, sulfonic acid group, or boric acid group, and at least one group among X1, X2, X3, X4, X5, X6, X7, and X8 is a phosphonic acid group, sulfonic acid group, carboxyl group, or boric acid group; Z is selected from the structure of Formula III ( ) and IV structure ( ),in, For the connection sites with the remainder of Formula II, M1 and M2 are each independently selected from C1-C4 alkyl groups; M3 is selected from substituted or unsubstituted C6-C14 aromatic groups, which are optionally substituted by 1, 2, 3, 4 or 5 substituents selected from hydroxyl, carboxyl, amino, methylthio, phosphonic acid, sulfonic acid and boric acid groups.

9. The photovoltaic device as described in claim 8, characterized in that, In Formula I, L1 and L2 are each independently 2,1,3-benzothiadiazole-4,7-diyl, phenylene, or absent.

10. The photovoltaic device as described in claim 8, characterized in that, In Formula II, X1, X2, X3, X4, X5, X6, X7, and X8 are each independently a hydrogen atom, hydroxyl group, carboxyl group, amino group, methylthio group, phosphonic acid group, sulfonic acid group, or boric acid group, and at least one group among X1, X2, X3, X4, X5, X6, X7, and X8 is a phosphonic acid group, sulfonic acid group, carboxyl group, or boric acid group; Z is selected from the structure of Formula III ( ) and IV structure ( ),in, For the connection sites with the remainder of Formula II, M1 and M2 are each independently selected from C1-C4 alkyl groups; M3 is selected from substituted or unsubstituted phenyl groups, which are optionally substituted by 1, 2, 3, 4 or 5 substituents selected from hydroxyl, carboxyl, amino, methylthio, phosphonic acid, sulfonic acid and boric acid groups.

11. The photovoltaic device as described in claim 8, characterized in that, Formula II is In formula V, X1, X2, X3, X4, X5, X6, X7 and X8 are each independently a hydrogen atom, hydroxyl group, carboxyl group, amino group, methylthio group, phosphonic acid group, sulfonic acid group or boric acid group; Among them, at least three groups in X1, X2, X3, X4, X5, X6, X7 and X8 are not hydrogen; and at least one group in X1, X2, X3, X4, X5, X6, X7 and X8 is a phosphonic acid group, a sulfonic acid group, a carboxyl group or a boric acid group.

12. The photovoltaic device as described in claim 8, characterized in that, Formula II is , In Formula VI, Y1, Y2, Y3, Y4, Y5, Y6, Y7, and Y8 are each independently a hydrogen atom, hydroxyl group, carboxyl group, amino group, or methylthio group; Y9 is a phosphonic acid group, sulfonic acid group, carboxyl group, or boric acid group; L3 is a C3-C12 heteroarylene, C6-C12 arylene, C1-C4 alkylene group, or is absent; wherein, at least one group among Y1, Y2, Y3, Y4, Y5, Y6, Y7, and Y8 is not hydrogen.

13. The photovoltaic device as described in claim 12, characterized in that, In Formula VI, L3 is phenylene, C1-C4 alkyl, or absent.

14. The photovoltaic device as described in claim 1, characterized in that, The self-assembled monomolecule material is selected from: , , and .

15. The photovoltaic device according to any one of claims 1-14, characterized in that, The photovoltaic device is a crystalline silicon-perovskite tandem cell.

16. The photovoltaic device as described in claim 15, characterized in that, The crystalline silicon-perovskite tandem solar cell comprises, from the back side to the front side, a crystalline silicon cell, a tunneling layer, a hole transport layer, an inorganic interface layer, a perovskite light-absorbing layer, an electron transport layer, a transparent conductive layer, and a metal electrode.

17. The photovoltaic device as described in claim 15, characterized in that, A perovskite passivation layer is further provided between the perovskite light-absorbing layer and the electron transport layer; and / or, The tunneling layer comprises a transparent conductive oxide.

18. A method for preparing a photovoltaic device according to any one of claims 1-17, characterized in that, The method includes: sequentially preparing a hole transport layer, an inorganic interface layer, and a perovskite light-absorbing layer on a conductive substrate; the inorganic interface layer is prepared by atomic layer deposition or chemical bath deposition; the temperature at which the inorganic interface layer is deposited is lower than the thermal decomposition temperature of the hole transport layer.

19. The method as described in claim 18, characterized in that, The conductive substrate includes a tunneling layer and optionally a crystalline silicon cell located on the side of the tunneling layer away from the light-receiving side.